(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2021)
Purpose: On the example of a regional self-government unit, the paper aims to provide additional evidence to support the notion that the application of a quality management system (QMS) in public administration produces positive change in organizational culture, improves business processes as well as the quality and delivery of services, etc., and, as such, is a necessary precondition for modernization and improvement of its efficiency. Methodology: International scientific and professional research shows that the application of quality management systems in public administration is a prerequisite for modernization and improvement of overall system efficiency. The paper gives an overview of the QMS implementation in public administration in the Republic of Croatia and presents the effects of the application of the international standard ISO 9001 in Osijek-Baranya County. Results: The results indicate that the application of QMS in Osijek-Baranya County has had significant effects on the operation of public administration. The most significant among them are financial savings, increased transparency, acceleration of business processes, etc. Conclusion: The application of a quality management system in public administration has produced positive effects especially in terms of improving (streamlining and speeding up the processes as well as increasing transparency of work thus providing an avenue towards modernizing and improving the overall efficiency of public administration.